2020
DOI: 10.1136/neurintsurg-2020-016416
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of ulnar artery access for neuroangiography and neurointervention: a case series

Abstract: BackgroundRadial access has become popular among neurointerventionalists because it has favorable risk profiles compared with femoral access. Difficulties in accessing or navigating the radial artery have been viewed as a reason to convert to femoral access, but ulnar artery access may prevent complications associated with transfemoral procedures.ObjectiveTo evaluate the safety and feasibility of ulnar access for neurointerventions and diagnostic neuroangiographic procedures.MethodsConsecutive patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For neurointerventional procedures, the trans-radial approach resulted in lower odds of complication than the trans-femoral approach 19. While there have not been many studies comparing trans-ulnar with trans-radial approach, a trans-ulnar approach is described as an alternative to trans-radial access 20. In randomized studies for coronary interventions, complication risks using trans-ulnar access were found to be close to trans-radial access 21 22.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For neurointerventional procedures, the trans-radial approach resulted in lower odds of complication than the trans-femoral approach 19. While there have not been many studies comparing trans-ulnar with trans-radial approach, a trans-ulnar approach is described as an alternative to trans-radial access 20. In randomized studies for coronary interventions, complication risks using trans-ulnar access were found to be close to trans-radial access 21 22.…”
Section: Discussionmentioning
confidence: 99%
“… 19 While there have not been many studies comparing trans-ulnar with trans-radial approach, a trans-ulnar approach is described as an alternative to trans-radial access. 20 In randomized studies for coronary interventions, complication risks using trans-ulnar access were found to be close to trans-radial access. 21 22 Therefore, success in deploying the Xience Skypoint using three different approaches demonstrate the stent’s flexibility, which gives providers the ability to perform their cases in a way that will be most beneficial to their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dossani et.al has published the only available dedicated case series utilizing TUA for neurovascular procedures. 17 It comprised eighteen patients with only limited interventional procedures. Recently Ahmad et.al published their institutional experience of 760 neuro-interventions performed via upper extremity access.…”
Section: Discussionmentioning
confidence: 99%
“…There is only one available case series comprising 18 patients regarding the use of TUA for cerebral angiography and neuro-interventional procedures. 17 Joshi et al recently published a review of literature including 1342 patients undergoing trans-radial approach for neuro-interventions. 64 out of 1342 patients (4.77%) had failed trans-radial approach and a crossover to trans-femoral access was made for the completion of procedure.…”
Section: Introductionmentioning
confidence: 99%